The Use of CRISPR/Cas9 Gene Editing to Confirm Congenic Contaminations in Host-Pathogen Interaction Studies - Ferrand, Jonathan; Croft, Nathan P.; Pépin, Geneviève; Diener, Kerrilyn R.; Wu, Di; Mangan, Niamh E.; Pedersen, John; Behlke, Mark A.; Hayball, John D.; Purcell, Anthony W.; Ferrero, Richard L.; Gantier, Michael P. (Frontiers in Cellular and Infection Microbiology, 2018)
Murine models of Salmonella enterica serovar Typhimurium infection are one of the commonest tools to study host-pathogen interactions during bacterial infections. Critically, the outcome of S. Typhimurium infection is impacted by the genetic background of the mouse strain used, with macrophages from C57BL/6 and BALB/c mice lacking the capacity to control intracellular bacterial replication. For this reason, the use of congenic strains, which mix the genetic backgrounds of naturally protected mouse strains with those of susceptible strains, has the capacity to significantly alter results and interpretation of S. Typhimurium infection studies. Here, we describe how macrophage knockout cell lines generated by CRISPR/Cas9 gene editing can help determine the contribution of background contaminations in the phenotypes of primary macrophages from congenic mice, on the outcome of S. Typhimurium infection studies. Our own experience illustrates how the CRISPR/Cas9 technology can be used to complement pre-existing knockout models, and shows that there is great merit in performing concurrent studies with both genetic models, to exclude unanticipated side-effects on host-pathogen interactions.